Revealing the Effect of Nanoscopic Design on the Charge Carrier Separation Processes in Semiconductor‐Metal Nanoparticle Gel Networks. Issue 1 (29th October 2021) - Schlenkrich, Jakob; Zámbó, Dániel; Schlosser, Anja; Rusch, Pascal; Bigall, Nadja C.
Abstract: In this paper, it is shown that the nanoscopic design of combining semiconductors and noble metals has a direct impact on the macroscopic (electrochemical) properties of their assembled, hyperbranched, macroscopic gel networks. Controlled and arbitrary deposition of gold domains on CdSe/CdS nanorods leads to tipped and randomly decorated heteroparticles, respectively. Structural and optical properties of the gel networks depend upon assembling the hybrid particles by means of oxidative or ionic routes. Additionally, the impact of different building block designs on the charge carrier separation processes is investigated from spectroelectrochemical point of view. A more efficient charge carrier separation is revealed in the tipped design manifesting in higher negative photocurrent efficiencies compared to the arbitrary decoration, where the charge recombination processes are more remarkable. This work sheds light on the importance of the nanostructuring on the spectroelectrochemical properties at the macroscale paving the way towards their use in photochemical reactions. Abstract : The effect of the nanoscopic design of hybrid semiconductor−noble metal nanoparticles on the structural and electrochemical properties of their assembled gel network structures is presented. Porous gel structures built up from CdSe/CdS nanorods decorated with Au domains randomly or only at their tip region are compared in terms of charge carrier dynamics using spectroelectrochemical tools upon illumination.